3D Cardiac Cell Culture: A Critical Review of Current Technologies and Applications - Zuppinger, Christian (Frontiers in Cardiovascular Medicine, 2019)
Three-dimensional (3D) cell culture is often mentioned in the context of regenerative medicine, for example, for the replacement of ischemic myocardium with tissue-engineered muscle constructs. Additionally, 3D cell culture is used, although less commonly, in basic research, toxicology, and drug development. These applications have recently benefited from innovations in stem cell technologies allowing the mass-production of hiPSC-derived cardiomyocytes or other cardiovascular cells, and from new culturing methods including organ-on-chip and bioprinting technologies. On the analysis side, improved sensors, computer-assisted image analysis, and data collection techniques have lowered the bar for switching to 3D cell culture models. Nevertheless, 3D cell culture is not as widespread or standardized as traditional cell culture methods using monolayers of cells on flat surfaces. The many possibilities of 3D cell culture, but also its limitations, drawbacks and methodological pitfalls, are less well-known. This article reviews currently used cardiovascular 3D cell culture production methods and analysis techniques for the investigation of cardiotoxicity, in drug development and for disease modeling.